EARTH AS A STABILIZATION AND CONSOLIDATION ELEMENT FOR BUILT-HERITAGE FOUNDATIONS: TWO CASE STUDIES IN BRAZIL - Puccioni, Silvia (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
This paper deals with the use of earthen materials in the consolidation/stabilization of monument foundations from experiments conducted between 2001 and 2004, whose design and implementation were coordinated by the author. For both cases, the author adopted the methodology of her master’s thesis, developed from her experience in conservation and restoration of historical Brazilian buildings. The case stud ies were characterized by characterist ic issure damage at t he foundations. Damage assessment was followed by trials and evaluation,which enabled diagnosis and the design of interventions for the project. The veriication of disaggregation and high moisture content of the soil, along with the results of physical characterization tests, substantiated the option for a system of recovery of the structural capacity of the foundations.This occurred through the substitution of the soil with Cyclopean rammed-earth blocks positioned laterally to the foundations, to attain their lateral coninement. This system was compatible with the overall behavior of buildings, whose foundations are direct, continuous and of low depth. The observation of current state of the two monuments proves that the system adopted was adequate to enhance the structural capacity, since there was no movement or deformation of the masonry. The intervention adopted in the case studies presented in this article preserves the integrity and the authenticity of the original foundation structure of the buildings. Moreover, it also allows its reversibility, as it can be removed without harming the historic building material.